Call for papers and instructions for authors for the issue 3-2024 (Vojnotehnički glasnik / Military Technical Courier, 2024)
The instructions to authors about the article preparation for publication in the Military Technical Courier are based on the Regulations on categorization and ranking of scientific journals of the Ministry of Education, Science and Technological Development of the Republic of Serbia (Official Gazette of the Republic of Serbia, No 159/20). This Regulations aims at improving the quality of national journals and raising the level of their compliance with the international system of scientific information exchange.
Keywords: Military Technical Courier; call for papers; instructions for authors